The battle for talent: Globalisation and the rise of executive pay - Dalia Marin (Bruegel, 2009)
Recent long-run time series evidence for the US suggests that popular explanations for the surge in executive pay are not supported by the data. This paper explores the role of globalization for the rise in executive pay based on new firm survey data on executives and their pay in Austria and Germany. I find that firms more exposed to international competition engage in talent fairs to search and attract skilled workers. Furthermore, I find that seniority related pay varies for different levels of foreign competition suggesting that firms increase CEO pay when faced with the threat of losing their senior executives to foreign competitors, while seniority in office itself does not lead to higher pay. These findings support the idea of a war for talent that is triggered by international trade, as suggested by recent theories of international trade and organisations.
Keywords: 330; Führungskräfte; Lohn; Internationaler Wettbewerb; Personalbeschaffung; Handelsliberalisierung; Deutschland; Österreich